2018
DOI: 10.1108/et-02-2018-0052
|View full text |Cite
|
Sign up to set email alerts
|

Muslim minority women in Western Thrace: any room for transformative learning?

Abstract: Purpose The purpose of this paper is to gain meaningful insights in the learning background, experiences and potential of Muslim minority women in Western Thrace. Design/methodology/approach Qualitative data were obtained through 12 semi-structured interviews, which underwent a three-level qualitative analysis, following the “grounded theory” methodology. Findings It was depicted that Muslim minority women in Western Thrace are susceptible to patriarchal gender norms governed by stereotypes that restrict w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Transformative learning is a learning strategy developed by Jack Mezirow and is generally applied to adult learning. Transformative learning can be defined as learning that emphasizes how to create cooperative and collective structures, systems, and processes needed for social democracy (Brewer et al, 2017;Panitsides & Kiouka, 2018;Spring et al, 2018). Transformative learning seen from the point of view of the student learning process can be defined as a behavioural process by which learners relate transformative experiences, focusing on what learners do, feel, and experience (Baldwin, 2019;Zaky, 2019).…”
Section: Literature Review Transformative Learning Conceptual Modelmentioning
confidence: 99%
“…Transformative learning is a learning strategy developed by Jack Mezirow and is generally applied to adult learning. Transformative learning can be defined as learning that emphasizes how to create cooperative and collective structures, systems, and processes needed for social democracy (Brewer et al, 2017;Panitsides & Kiouka, 2018;Spring et al, 2018). Transformative learning seen from the point of view of the student learning process can be defined as a behavioural process by which learners relate transformative experiences, focusing on what learners do, feel, and experience (Baldwin, 2019;Zaky, 2019).…”
Section: Literature Review Transformative Learning Conceptual Modelmentioning
confidence: 99%
“…Disorientation likely occurs when individuals encounter challenges in their life (Apte, 2009;D'Amato & Krasny, 2011;Mezirow, 1991;Morgan, 2010). Those challenges include dealing with tough issues (Parks Daloz, 2000;Panitsides & Kiouka, 2018), difficult problems (Pennington et al, 2013), critical incidents (Addleman et al, 2014), a life crisis Mezirow, 1978;Taylor, 1994) or culture shock (Morgan, 2010;Taylor, 1994). The intensity of these experiences forms the core of disorientation (Apte, 2009;Taylor, 2000).…”
Section: A Disorienting Dilemma In Transformative Learningmentioning
confidence: 99%
“…Our research on the participation of disadvantaged social groups in AE (Panitsides, 2013(Panitsides, , 2017Panitsides & Kiouka, 2018;Panitsides, Loti Papastamatis & Valcanos, 2016;Papastamatis & Panitsides 2009) has indicated that it takes comprehensive approaches demanding effort, time, resources, and expert knowledge to overcome the various situational, dispositional and institutional barriers (Cross, 1981), with the dispositional ones identified to exert principal influence on the "non-learners" (UNESCO, 2019). If the aim is to substantially raise participation in AE among individuals least prepared or inclined, or with little opportunity to learn, policies should ensure ample financial resources and draw on concrete measures that may help AE reach out to the unreached, such as:…”
Section: Recommendations: a Model Of Want Not Needmentioning
confidence: 99%